Sixth Sense on Personal Assistance (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper mainly focuses on dealing with  the problems faced by the deaf and the dumb community in  India in using the future technologies mainly personal  assistance tools, may it be Alexa home or Amazon echo. We  propose to make use of the standard Indian sign language as  well as the sign language dictionary to create a manual  entries of sign languages to a user interface which makes  use of these sign language dictionary to convert the signs  shown by a speech or noise impaired person by taking  inputs from digital cameras or the laptop cameras in order  to convert them into speech and made useful to the personal  assistance tools that just takes audio voice as inputs. It is  built by using machine learning tools which includes a  TensorFlow library package. The whole project is user  made to be user friendly to the community that will make  use of it the most as well as easily understandable by the  personal assistance tools in use worldwide. The project  promises to ease the work of a speech disabled individual  may it be through easy conversion of sign languages for a  video call which helps the receiver get written transcripts of  the signs displayed by the individual on the other end.  However the main purpose of the project is with the purpose  of helping such individuals make use of personal assistance  tools which poses as an essential tool in the future to come.
Keywords: TensorFlow; Sign Language Dictionary and Indian Sign Language